2017
DOI: 10.1080/15384101.2017.1320629
|View full text |Cite
|
Sign up to set email alerts
|

p53R2 overexpression in cervical cancer promotes AKT signaling and EMT, and is correlated with tumor progression, metastasis and poor prognosis

Abstract: p53R2 is a p53-inducible ribonucleotide reductase subunit involved in deoxyribonucleotide biosynthesis and DNA repair. Although p53R2 has been linked to human cancer, its role in cervical cancer remains unknown. In this study, we investigated the expression and clinical significance of p53R2 in early-stage cervical cancer. p53R2 expression is significantly upregulated at both mRNA and protein levels in cervical cancer cells and tissues, compared with that in matched normal cervical cells and tissues, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…[19][20][21] Moreover, it has been confirmed that activated PI3K/AKT is correlated with the progression and metastasis of cervical cancer cells. [22] In this study, knockdown of USP18 deeply suppressed the phosphorylation of AKT in cervical cancer cells. The PI3K/AKT inhibitor LY294002 deeply suppressed the function of oeUSP18 in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 61%
“…[19][20][21] Moreover, it has been confirmed that activated PI3K/AKT is correlated with the progression and metastasis of cervical cancer cells. [22] In this study, knockdown of USP18 deeply suppressed the phosphorylation of AKT in cervical cancer cells. The PI3K/AKT inhibitor LY294002 deeply suppressed the function of oeUSP18 in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, it also plays an oncogenic role. 29,30 In the present study we attempted to prove that cell proliferation, migration, and invasion facilitated by DGCR8/ZFAT-AS1 in vitro might be ascribed to PRC2-induced H3K27me3 modification in the CDX2 promoter region. Additionally, we aimed to elucidate whether DGCR8 and ZFAT-AS1 played an important role in the progression of glioma.…”
Section: Introductionmentioning
confidence: 97%
“…Epithelial-mesenchymal transition (EMT) is one of the main causes of cancer metastasis 29 . EMT-activated transcription factors are invasive and motility characteristics for cervical cancer 30…”
Section: The Association Of Otud5 Expression With Clinicopathologic Cmentioning
confidence: 99%
“…2H). In cervical cancer, activation of PI3K-AKT signaling is closely related to tumor progression and poor prognosis30 . Consistently, OTUD5 is also downregulated in PI3K-AKT related subtypes(FIG.…”
mentioning
confidence: 99%